The goat from the southwest in Theodotion’s Daniel translation, Theodoret’s commentary, and the Alexander romance - Garstad, Benjamin (My University, 2017)
According to Theodotion’s translation of the Book of Daniel, in one of Daniel’s visions a he-goat, interpreted as the king of Greece, is said to attack a ram, the king of Media and Persia, from the southwest, while the Septuagint translation says from the west. Theodoret of Cyrrhus, basing his commentary on Theodotion’s translation, explains this verse as referring to Alexander’s march from Egypt to his final battle against Darius at Gaugamela. In so doing, he must disregard the remainder of Alexander’s campaign against the Persians (of which he is clearly aware). He also eschews as a source the Alexander Romance, which offered a point of origin for Alexander’s attack on the Persian Empire perfectly consistent with Theodotion’s ‘from the southwest’, but was thoroughly unreliable as an historical source. It is possible, nevertheless, that the translation of Theodotion was itself influenced by the Alexander Romance on this point.
Keywords: Book of Daniel; Theodotion; Septuagint; Theodoret of Cyrrhus; Alexander Romance